ROLAND BARTHES' SEMIOTIC ANALYSIS OF THE MEANING OF HARAM IN THE QURAN - Makarim, Muhmmad Ghifari; Rahayu, Hikmawati; Mardi, Mulia (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this research is to find meanings that are in accordance with the context of meaning at the time when the Qur'an was revealed and take the main message (significance) contained in the meaning to be contextualized in the present with appropriate meaning. Through the existing problem the word haram is often interpreted as a word prohibition, this understanding starts from the meaning of haram in the translation of the Qur'an itself but in fact the word haram itself has another meaning when presented in a textually different letter metamorphose. This research will be presented through Roland Barthes' linguistic semiotics research method by examining the word haram through a Semiotics approach. This analysis will be through the search for the meaning of Connotation and Denotation which explains the disclosure of myths behind a sign or writing. The results of this study produced an analysis of new meanings related to the word haram. This haram word algorithm changes its nature depending on the text and context of the verse. Not when haram is said to be a prohibition, but in this myth it turns out to have other meanings such as haram is an antonym of the word halal which means halal is in its place, while haram is not a prohibition but not in its place or limitation.